Community structure analysis of phytoplankton as an indicator of mangrove ecosystem health - Hilaluddin, Fareha (2022)
Mangrove ecosystems are substantial to water quality management as it helps to improve water quality by absorbing pollutants from runoff. Unfortunately, deforestation of mangroves in Malaysia are in a critical state due to the development of urban population and currently prompted to several issues. Lack of sustainable mangrove management in addition to high anthropogenic pollutants from runoff could lead to marine eutrophication and subsequently distressed the biological communities. The occurrence of phytoplankton is particularly an important ecological indicator in accessing mangrove ecosystem health since phytoplankton react as a key role for mangrove productivity that form essential base of oceanic food webs. Phytoplankton community species can define the major functional groups that ultimately influence ecosystem pollution due to the occurrence of harmful algae blooms. This study was aim to identify the phytoplankton communities uses as bioindicators of mangrove estuarine areas. In this study, phytoplankton communities and its regional physicochemical parameters were explored to identify the potential uses of phytoplankton as a reliable indicator of mangrove ecosystem, as well as to formulate a phytoplankton-based index to access mangrove pollution. Two major locations of the Matang mangroves of Perak and the Pendas mangroves of Johor had been selected, representing various mangrove disturbance and pollution levels. Rivers namely Tiram Laut, Tinggi and Sepetang (located in the Matang mangroves of Perak) while Pendas (located in the Pendas mangroves of Johor) were classified based on ground truth to represent the pristine mangroves of the least disturbance (Tiram Laut), moderately disturbance (Tinggi), high disturbance (Sepetang) and highly degraded area with very high disturbance (Pendas). In situ water parameters and water samples for phytoplankton enumeration, chlorophyll a, total solids and water nutrients were collected monthly for one-year cycle using 5L Niskin water sampler. Phytoplankton abundance and composition to the lowest taxa were investigated using Sedgewick Rafter counting chamber, while water nutrients analyses were done based on standard methods using spectrophotometric analysis. Among phytoplankton groups, diatoms and dinoflagellates were the main phytoplankton groups that represented as the highest densities contributed >60% of the total phytoplankton community in all stations. A centric diatom, Skeletonema costatum was a major diatom species found in the moderately disturbed, highly disturbed and highly degraded area, blooms at the higher rate constituting 64.6% of the mean total phytoplankton which showed increased densities with the increasing level of disturbance. The survivals of Skeletonema species in the moderately disturbed area (1.14 x 105 cells/L) were associated to temperature and total nitrogen (p < 0.05), while turbidity was significantly in highly reclaimed area as the blooms occurred during dry weather of the northeast monsoon season. On the other hand, Cyclotella choctawhatcheeana has indicated the pristine area, controlled by transparency and salinity, while small temperature elevation and eutrophication had led to dinoflagellates blooms of Protoperidinium acutum in the highly disturbed mangrove area. Dissimilar phytoplankton community structure was noted in the highly degraded mangrove area of the Pendas mangrove Johor, due to the occurrence of numerous harmful dinoflagellates blooms including Peridinium quinquecorne, Karenia sp., Prorocentrum lima, and Karlodinium australe. The harmful unarmored Karlodinium australe and a centric diatom Skeletonema costatum were main phytoplankton group occurred in the highly degraded mangrove area associated to the total dissolved solids and nutrients (p < 0.05). The present study suggested that the phytoplankton biodiversity declines and the abundance of harmful species increased with increasing disturbance levels. Based on the phytoplankton community data within different levels of mangrove disturbance, the best four metrics were concluded using PCA tool for the development of the Phytoplankton-Blooms Class Index (PbCI). Phytoplankton indicators based on cells formation or types of species blooms recorded were ranked from 1 to 5 in order to assess mangrove ecosystem health. This study illustrated the changes in phytoplankton community which influenced by disturbance that significantly important to indicate the status of mangrove ecosystem health.